Anthropometric profiles of elite athletes - Cullen, S.; Fleming, J.; Logue, D. M.; O`Connor, J.; Connor, B.; Cleary, J.; Watson, J. A.; Madigan, S. M. (Journal of Human Sport & Exercise, 2022)
Quantifying body composition is central to monitoring performance and training in athletes, however limited sport-specific anthropometric reference data, assessed and reported in a standardised manner, is available. This study provides anthropometric profiles in elite male athletes from different sports. Elite male athletes (n = 73) from National squads of boxing (n = 10), cricket (n = 21), swimming (n = 23), hockey (n = 10) and eventing (n = 9) were assessed for body mass, height, eight skinfolds (triceps, subscapular, biceps, iliac crest, supraspinal, abdominal, thigh and medial calf), body circumferences (arm, waist, hip, thigh and calf) and muscle circumferences (arm, thigh, calf) using ISAK standardised guidelines. For all athletes, large variability exists for measures of skinfold thickness at each skinfold site. Swimming (64.6 ± 16.1 mm) and boxing (63.5 ± 16.1 mm) were similar for the sum of eight skinfolds (Sigma8SKF) but swimming had lower Sigma8SKF compared to cricket (86.1 ± 21.3 mm; p = .011) and eventing (89.9 ± 30.7 mm; p = .028). Hockey (81.9 ± 26.3 mm) and eventing had the most varied Sigma8SKF. Thigh body (p=.006) and muscle circumferences (p = .005) were significantly reduced in boxing compared to hockey. No differences were seen between sports for arm (p = .346; ES = .06) and calf (p = .382; ES = .06) muscle circumferences. The anthropometric profiles for elite athletes from various sports during pre-season training will be a useful resource for sports professionals when monitoring and interpreting body composition data. Large variation exists in anthropometric profiles between the different athletes and different sports, highlighting the necessity to have sport-specific normative ranges available to allow optimal monitoring of individual athletes particularly varying across sports as well as age, training status and position.